2017
DOI: 10.24815/siele.v4i2.6351
|View full text |Cite
|
Sign up to set email alerts
|

“That’s the biggest impact!” Pedagogical values of movies in ELT classrooms

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…On the one hand, using movies to teach English can increase students' enthusiasm for learning a new language and improve the classroom environment (Guan et al, 2018). Han (2019) suggested that the way and process of language learning must relate to cultural learning as an essential aspect because Ismail (2017) states that the language aspect most affected by watching movies was the cultural aspect. Language is the process of what is received from, what is read, and the social environment sector.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, using movies to teach English can increase students' enthusiasm for learning a new language and improve the classroom environment (Guan et al, 2018). Han (2019) suggested that the way and process of language learning must relate to cultural learning as an essential aspect because Ismail (2017) states that the language aspect most affected by watching movies was the cultural aspect. Language is the process of what is received from, what is read, and the social environment sector.…”
Section: Introductionmentioning
confidence: 99%
“…For example, YouTube provides many English video clips for students to learn vocabulary. Moreover, films and videos are practical ways to motivate and assist students in understanding language (Baltova, 1999;Ismail, 2017;Zanón, 2007). Similarly, Donaghy (2014) asserted that learning through films/videos is encouraging and fun.…”
Section: Video Subtitle For Efl Instructionmentioning
confidence: 99%
“…The integration of ICT into language teaching varies in terms of implementation. Some studies, particularly on speaking skill development, have investigated ICT as media to present learning materials interactively (Asnawi, 2015;Fauzi, 2016;Ismail, 2017;Kusuma,…”
Section: Introductionmentioning
confidence: 99%